Exon recognition and nucleocytoplasmic partitioning determine AMPD1 alternative transcript production. - Mineo, I (1991)
Two mature transcripts are produced from the rat AMP deaminase 1 (AMPD1) gene, one that retains exon 2 and one from which exon 2 has been removed. The ratio of these two transcripts is controlled by stage-specific and tissue-specific signals (I. Mineo, P. R. H. Clarke, R. L. Sabina, and E. W. Holmes, Mol. Cell. Biol. 10:5271-5278, 1990; R. L. Sabina, N. Ogasawara, and E. W. Holmes, Mol. Cell. Biol. 9:2244-2246, 1989). By using transfection studies with native, mutant, and chimeric minigene constructs, two steps in RNA processing that determine the ratio of these two transcripts have been identified. The first step is recognition of this exon in the primary transcript. The primary transcript is subject to alternative splicing in which exon 2 is either recognized and thereby included in the mature mRNA or is ignored and retained in a composite intron containing intron 1-exon 2-intron 2. The following properties of the primary transcript influence exon recognition. (i) Exon 2 is intrinsically difficult to recognize, possibly because of its small size (only 12 bases) and/or a suboptimal 5' donor site at the exon 2-intron 2 boundary. (ii) Intron 2 plays a permissive role in recognition of exon 2 because it is removed at a relatively slow rate, presumably because of the suboptimal polypyrimidine tract in the putative 3' branch site. The second step in RNA processing that influences the ratio of mature transcripts produced from the AMPD1 gene occurs subsequent to the ligation of exon 2 to exon 1. An RNA intermediate, composed of exon 1-exon 2-intron 2-exon 3, is produced in the first processing step, but it is variably retained in the nucleus. Retention of this intermediate in the nucleus is associated with accumulation of the mature mRNA containing exon 2, while cytoplasmic escape of this intermediate is reactions, exon recognition and nucleocytoplasmic partitioning, determine the relative abundance of alternative mRNAs derived from the AMPD1 gene.